Perancangan Aplikasi TeamKickOff Turnamen Futsal Berbasis Mobile Design Thinking - Hariyadi, Dyon Fillipo Agma; Olivia; Mawarni, Marselyna Fitri; Wijaya, Novan (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The Student Activity Unit (UKM) for Futsal at Multi Data Palembang University often experiences obstacles in tournament management, such as delays in match information updates, difficulty accessing information by participants, data recording errors, and inefficient time for compiling match brackets. This research aims to design a mobile-based futsal tournament management application called TeamKickOff using the Design Thinking method through five stages: empathize, define, ideate, prototype, and test. In the empathize stage, in-depth interviews were conducted with 12 respondents, participatory observation, and document analysis. The define stage produced an empathy map, user persona, point of view, and user journey map. The ideate stage involved brainstorming, card sorting, and wireframe development. Prototypes were developed in three versions (low, mid, and high-fidelity) with features for schedule management, real-time score recording, automatic match brackets, and video documentation. Usability testing with 32 respondents resulted in a SUS score of 78.6 with a task completion rate of 91.3% and a reduction in management time of up to 65% compared to manual methods. The research results show that the TeamKickOff application successfully improved the efficiency of futsal tournament organization and information access for participants, with advantages in video documentation integration and focus on the local campus context in Indonesia.